An improved reactivity-equivalent physical transformation for treating FCM fuel with burnable poisons. (November 2018) - Li, Jian; She, Ding; Shi, Lei
Highlights: The conventional RPT method arises high deviation in treating the FCM fuel with BP. An improved RPT method is proposed to treat the FCM fuel with burnable poisons. The IRPT method is applicable in both criticality calculations and burnup calculations. The IRPT method is found insensitive to operation parameters. Abstract: In recent years, the fully ceramic microencapsulated (FCM) fuel is employed in some advanced Pressurized Water Reactors (PWR) to achieve a high fuel performance. In the FCM fuel, TRISO coated particles are randomly distributed in the matrix material, which leads to the so-called double-heterogeneity effect. In previous studies, the reactivity-equivalent physical transformation (RPT) was proposed to handle the double-heterogeneity of the FCM fuel. The RPT method is easy-to-implement and gives excellent accuracy in the FCM fuel without burnable poisons. However, when the FCM fuel is filled with both fuel particles and burnable poison particles, the RPT method is found to produce significant deviations. Therefore, an improved reactivity-equivalent physical transformation (IRPT) method is proposed in this paper to accurately treat the FCM fuel with burnable poison particle. Numerical tests suggest that the IRPT method is applicable in both criticality and burnup calculations, and it is insensitive to operation parameters.